2004
DOI: 10.1063/1.1790559
|View full text |Cite
|
Sign up to set email alerts
|

A new plasma potential measurement instrument for plasma ion sources

Abstract: A very efficient and fast instrument to measure the plasma potential of ion sources has been developed at the Department of Physics, University of Jyväskylä (JYFL). The operating principle of this novel instrument is to apply a decelerating voltage into a mesh located in the beamline of the ion source. The plasma potential is determined by measuring the current at the grounded electrode situated behind the mesh as a function of the voltage. In this article, we will introduce the instrument and the first result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 10 publications
2
33
0
Order By: Relevance
“…4. Additionally, we investigate the effect of gas mixing on the plasma potential with the same method.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…4. Additionally, we investigate the effect of gas mixing on the plasma potential with the same method.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, several laboratories measured the plasma potential and reported the importance of the measurement, because the lower plasma potential gives us the higher beam intensity of the highly charged heavy ions. [3][4][5] One of the new methods for plasma potential measurement is based on the retarding electric field and successfully applied to measure the plasma potential of ECR ion sources under various conditions ͑gas pressure, rf power, and gas mixing͒. 4,5 In our previous work, we observed that the beam intensities of the highly charged heavy ions are strongly dependent on the B min .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a significant energy spread can influence the longitudinal optics, it was felt necessary to measure the plasma potentials for various ions and its dependance on source tuning parameters. Tarvainen et al, 6 have measured plasma potentials using the retarding field technique and observed the plasma potentials to increase with RF power and gas pressure and the values changed when the negative dc bias was varied. Tarvainen et al, 7 also measured the the effect of the gas mixing technique on the plasma potential, energy spread, and emittance of the beam under various source conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting part of our work is the plasma potential measurements [1]. The main object of the JYFL ion source group is to serve the research program of the laboratory.…”
Section: Introductionmentioning
confidence: 99%